Water Quality Analysis Based on Chemical and Physical Parameters in the Acai River, Jayapura City - Bungasalu, Benny Abraham; Anou, Kezia; Sinaga, Ego Srivajawaty; Ngaderman, Hubertus; Sinaga, Novianti; Bunga', Martina (Photon: Jurnal Sain dan Kesehatan, 2024)
The Acai River functions as a primary channel located in the middle of Abepura City, which ends downstream at Yotefa Bay. The presence of various anthropogenic activities can provide a pollution burden to the environment, one of which is the decline in river water quality. This study aims to determine the water quality of the Acai River in Jayapura City. The study was conducted by collecting data through surveys and taking river water samples at six points. The parameters studied included temperature, water color, pH, TDS, DHL, BOD, and COD. The results of the study showed that the concentrations that exceeded the class II water quality standard limits, namely the BOD and COD concentrations at stations 1, 2, 3, 4, 5, and 6 exceeded the quality standard limits. Based on the Pollution Index value, at stations 1, 2, 3 the conditions were lightly polluted, while the conditions at stations 4, 5, 6 were classified as moderately polluted. It can be concluded that from upstream to downstream the water quality of the Acai River has increased in its water quality parameters